Od Biegunów do Prowadź swój pług przez kości umarłych – kilka uwag dotyczących recepcji fabularnego świata Olgi Tokarczuk w Rumunii - Godun, Cristina (Postscriptum Polonistyczne, 2020)
This paper presents the most important aspects of the reception of four novels by Olga Tokarczuk translated into Romanian, on the basis of reviews published in the Romanian literary press. The topics addressed most frequently by Romanian reviewers include the topos of journey, the contemporary human condition within the framework of everyday life, the axiological system of Olga Tokarczuk’s narrative world, the rich imagination, the fragmentary narrative, and the tendency to cross interdisciplinary boundaries. An amazing imagination, an exceptional literary talent, surprising combinations and multifaceted protagonists are only some of the elements of Olga Tokarczuk’s writing praised by Romanian reviewers. Tokarczuk’s novels are appreciated in Romania due to both the relevance of their themes, however uncomfortable they might be, and their great ability to translate such tough topics into literature.